2023
DOI: 10.1186/s13073-023-01170-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel transcriptional signature identifies T-cell infiltration in high-risk paediatric cancer

Abstract: Background Molecular profiling of the tumour immune microenvironment (TIME) has enabled the rational choice of immunotherapies in some adult cancers. In contrast, the TIME of paediatric cancers is relatively unexplored. We speculated that a more refined appreciation of the TIME in childhood cancers, rather than a reliance on commonly used biomarkers such as tumour mutation burden (TMB), neoantigen load and PD-L1 expression, is an essential prerequisite for improved immunotherapies in childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…First, it was found that the mutation frequency of all 4 driver genes of PC (KRAS, TP53, CDKN2A, SMAD4) were significantly elevated in the IL1R2 high expression group. Additionally, TMB, a biomarker closely associated with improved immunotherapies, [ 48 ] was proved to be increased in the IL1R2 high expression group. Combined with the IPS algorithm, it was found that patients in IL1R2 high expression possessed a relatively higher probability of responding to anti-PD1 therapy, anti-CTLA4 therapy and the combination of anti-PD1 and anti-CTLA-4 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was found that the mutation frequency of all 4 driver genes of PC (KRAS, TP53, CDKN2A, SMAD4) were significantly elevated in the IL1R2 high expression group. Additionally, TMB, a biomarker closely associated with improved immunotherapies, [ 48 ] was proved to be increased in the IL1R2 high expression group. Combined with the IPS algorithm, it was found that patients in IL1R2 high expression possessed a relatively higher probability of responding to anti-PD1 therapy, anti-CTLA4 therapy and the combination of anti-PD1 and anti-CTLA-4 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular profiling of the immune microenvironment of high-risk pediatric tumors based on Immune Pediatric Signature Score (IPASS), which combines immunohistochemistry staining data of T lymphocytes with RNA and whole-genome sequencing, estimated that 31% of high-risk cancers in pediatric patients have infiltrating T cells [ 23 ]. In CNS tumors, pediatric gliomas have the most T-cell receptor (TCR) clones, while osteosarcoma and neuroblastoma show more diversity in these clones.…”
Section: Profiling the Immune Microenvironment Of Pediatric Tumorsmentioning
confidence: 99%
“…This diversity in TCR repertoires is linked to prognosis and response to immune therapy in these tumors. Interestingly, the study found that tumor mutational burden (TMB) and neoantigen load, which reflect genetic changes in cancer cells, did not predict T-cell infiltration in pediatric cancers [ 23 ]. This implies that the presence of a high TMB or a large number of neoantigens may not necessarily correlate with increased T-cell infiltration and immune response in these cancers.…”
Section: Profiling the Immune Microenvironment Of Pediatric Tumorsmentioning
confidence: 99%
“…[ 72 ] scanned the entire immune microenvironment and found a decreased number of intratumoral‐activated Tregs in MPR tumors, along with clonal expansion of peripheral cytotoxic CD8 + T cells. Another study revealed therapy‐promoting expansion of cytotoxic T cells and activation of memory CD8 + T cells into an effector phenotype, as well as MPR‐associated reduction of neutrophil heterogeneity in the aged CCL3 + neutrophil/secreted phosphoprotein 1(+)/tumor‐associated macrophage pathway [ 73 ].…”
Section: Resectable La‐nsclcmentioning
confidence: 99%